Water quality Part 2. Physical, chemical and biochemical methods Sec 2.40 Method for the determination of borate by spectrometry using azomethine - H (BSI, 1991)
Water, Quality, Water testing, Determination of content, Chemical analysis and testing, Boron, Borates, Interferences (chemical), Concentration (chemical), Spectroscopy, Complexing methods, Test equipment, Sampling methods, Contamination, Calibration, Precision, Formulae (mathematics)